Hematopoietic stem cell transplant–associated thrombotic microangiopathy: review of pharmacologic treatment options. Issue 2 (11th September 2014) - Kim, Sara S.; Patel, Monank; Yum, Kendra; Keyzner, Alla
<x xml:space="preserve">Abstract</x> Background Transplant‐associated thrombotic microangiopathy (TA‐TMA) is a multifactorial disorder, which occurs as a result of treatment‐related endothelial injury and underlying disease process after hematopoietic stem cell transplantation (HSCT). The reported incidence of TA‐TMA after HSCT is 0% to 74% and has shown to be associated with mortality rate of up to 100%. TA‐TMA is often diagnosed late in the disease progression, and therapeutic plasma exchange (TPE) has not been shown to produce a high response rate. Study Design and Methods All English‐language articles describing pharmacologic treatments for TA‐TMA were identified using Ovid in the Medline database (1966‐May 2014). Search was limited to the HSCT population. Results Approximately 50% to 63% of patients with TA‐TMA respond to withdrawal of the offending agent (calcineurin inhibitors) and TPE, and many will require additional treatment to better control the disease. Unfortunately, there is no established treatment strategy for TA‐TMA. A number of pharmacologic agents that have been explored for the treatment of TA‐TMA include rituximab, vincristine, defibrotide, pravastatin, and eculizumab. The overall response rates of these agents were similar (69%‐80%); however, the differences in the treatment costs vary significantly between these agents. Defibrotide is an investigational agent in the United States; therefore, it is not readily available for use. Conclusion Larger studies are warranted to validate the role of these pharmacologic agents in TA‐TMA as upfront therapy and in TPE‐refractory patients. Recently suggested predictive biomarkers for TA‐TMA, such as neutrophil extracellular traps and circulating endothelial cells, deserve more attention in future studies.